Kekuatan Simbolik Beras dalam Ritus Kehidupan Masyarakat Batak Toba - Resmi Hutasoit; Izak M. Lattu; Ebenhaizer I Nuban Timo (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2020)
This article aims to analyze the background or history of rice used as a symbol of spirit strengthening in the rites of life stages in the Batak land which are carried out in the adat of marriage, free from distress, promotion, entering a new home also when the child is baptized. The method used is a qualitative method with interview, observation and literature study techniques. The results found that rice has a sacred value for the Batak people. Rice is generally owned by the rich and poor so that there is social equality so that using rice as a symbol of spirit strengthening. Rice provides physical needs for health. Human physical health is very influential on the human spirit. When giving rice in certain events there is an element of safety, when the rice is placed over the head and scattered. They use rice as a symbol in certain rites from generation to generation from their ancestors. Rice for the Batak has a very high historical value from the process of planting rice to rice. This paper contributes to traditional leaders and young people to preserve and understand the traditions of their ancestors.